EFEKTIVITAS PROGRAM PEJUANG MUDA DALAM PENGENTASAN KEMISKINAN DI KOTA SURABAYA - Amelia Jihan Fahnanda; Ruth Theda Rahmadevi; Moch. Faizal Syahputra; Kalvin Edo Wahyudi (Journal Publicuho, 2021)
This study aims to determine the effectiveness of the Youth Fighters Program in Poverty Alleviation in the City of Surabaya. This study used a qualitative descriptive method with data collection techniques through interviews with the population control office, the empowerment of women and children in the city of Surabaya and the researcher directly observed the young warrior program which was then written in an observation book. Sources of data from this study were also obtained through library research with the help of internet media and related journals. Based on the results of research on the effectiveness of the Young Fighters Program in poverty alleviation in the City of Surabaya, it is quite effective, when compared to before the existence of the Young Fighters program which was then analyzed using effectiveness theory which consists of indicators of the effectiveness of a program including efficiency, adequacy, equity, responsiveness, and accuracy although there are still indicators that need to be addressed. This can be a consideration for the government to continue to improve the program of young fighters in order to be able to alleviate poverty in the city of Surabaya